Antibiotic-Resistant Profiles of Bacteria Isolated from Cesarean and Surgical Patients from Kasese District Hospitals Western Uganda - Abraham Bwalhuma Muhindo; Adamu Almustapha Aliero; Martin Odoki; Ibrahim Ntulume; Emmanuel Eilu; Joe Mutebi; Yap Boum II; Richard Onyuthi Apecu (Borneo Journal of Pharmacy, 2021)
Surgical site infections (SSIs) are challenging to treat and often associated with much higher extended stays, morbidity, and mortality, higher treatment costs, especially when the causative agent is multidrug resistance (MDR). This study was designed to determine the prevalence of nosocomial infections and susceptibility profiles of bacteria isolated from Cesarean section (C-section) and surgical patients from Kasese District Hospitals in Western Uganda. A descriptive cross-sectional study was conducted from January to September 2016 involving 303 patients with SSIs in obstetrics & gynecology; and general surgery wards in three health facilities. Clinical-demographic characteristics of patients were obtained using structured questionnaires before surgery. Bacterial analysis of the air and floor of the theatre room was done using the standard culture method. Of the 303 patients enrolled with SSIs (median age 34 years), 71.6% were female, and 28.4% were males. Only 14.5% developed SSIs, with predominant isolates being Staphylococcus aureus 33.33% and Escherichia coli 24%. The majority of recruited participants underwent a C-section of 58% and the least amputations of 0.3%. Duration of operation or surgery, p-value 0.002 (95% CI 1.599-7.667) was significantly associated with SSIs. Gram-negative bacteria were found resistant (50-100%) to ampicillin, gentamycin, and ciprofloxacin, the commonly used post-operative drugs of choice. Hospital-acquired infections were common with emerging antibiotic-resistant strains isolated in most SSIs at Kasese hospitals. The development of resistance to commonly used antibiotics such as ampicillin, gentamycin, and ciprofloxacin than previously reported calls for laboratory-guided SSIs therapy and strengthening infection control policies.